Patterns of Care and Survival of Cutaneous Angiosarcoma of the Head and Neck. (11th February 2020) - Chang, Clifford; Wu, S. Peter; Hu, Kenneth; Li, Zujun; Schreiber, David; Oliver, Jamie; Givi, Babak
Abstract : Objective: To analyze the patterns of care and survival of cutaneous angiosarcomas of the head and neck. Study Design: Retrospective cohort study. Setting: National Cancer Database. Methods: The National Cancer Database was queried to select patients with cutaneous angiosarcoma of the head and neck between 2004 and 2015. For survival analysis, patients were included only if they received definitive treatment and complete data. Prognostic factors were analyzed by univariate and multivariable Cox regression. Results: We identified 693 patients diagnosed with head and neck angiosarcomas during the study period. The majority were male (n = 489, 70.6%) and elderly (median, 77 years). A total of 421 patients (60.8%) met the criteria for survival analyses. These patients were treated with surgery and radiation (n = 178, 42.3%), surgery alone (n = 138, 32.8%), triple‐modality therapy (n = 48, 11.4%), surgery and chemotherapy (n = 29, 6.9%), and chemoradiation (n = 28, 6.7%). With a median follow‐up of 29 months, the 3‐year survival was 50.1%. Patients undergoing surgery had better median survival than those who did not (38.1 vs 21.0 months, P =. 04). Age, comorbidity, tumor size, and surgical margins were significant factors in univariate analyses. On multivariable analysis, age ≥75 years (hazard ratio, 2.65; 95% CI, 1.80‐3.88; P <. 001) and positive margins (hazard ratio, 1.91; 95% CI, 1.44‐2.51; P <. 001) predicted worse overall survival. Conclusion: Angiosarcoma of head and neck is a rare malignancy that affects the elderly. Surgical treatment with negative margins is associated with improved survival. Even with curative‐intent multimodality treatment, the survival of patients aged ≥75 years is limited.